Efficacy of Bacillus thuringiensis, mineral oil, insecticidal emulsion and insecticidal gel against Phyllocnistis citrella Stainton (Lepidoptera: Gracillariidae) - Behnam Amiri-Besheli (Plant Protection Science, 2008)
The efficacy of Bacillus thuringiensis, mineral oil, insecticidal emulsion (garlic extract, plant detergent soap and food additive) and insecticidal gel (plant oil and plant extracts) to control the citrus leafminer, Phyllocnistis citrella, was examined in laboratory conditions 24, 48, 72 and 96 h after treatments. Leaves of citrus with second and third instars of leafminer larvae were used in all experimental tests. There were significant differences in larvae mortality between control and treatments (P < 0.0001), but no significant differences were found among treatments. Larvae mortality (%) in IE, IG, BT and MO was 67.83 ± 9.10, 62.45 ± 8.10, 49.08 ± 6.70 and 37.70 ± 8.50, respectively. The levels of mortality of larvae 96 and 72 h after treatments were higher than after 48 and 24 hours. The results indicate that 3 days is the maximum period of efficacy for all tested insecticides. In conclusion, the present study showed that under heavy infestation, use of synthetic insecticides is necessary to prevent reinfestation by the citrus leafminer.